“Tailored” Country Strategies in the U.S. Nuclear Posture Review - N. I. Bubnova (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2018)
The new Nuclear Posture Review (NPR), published in January 2018, stipulates a “tailored” strategy towards each country  which  Washington  sees as presenting a nuclear challenge to the United States. Yet  each “tailored”  strategy is based on the same reiterated assumption that the U.S. measures and programs are developed in response to external hostile actions. The NPR cites other countries’ aggressive behavior and military buildup as the reason to reinstitute the role of nuclear weapons as the key component of the U.S. deterrent, modernize the U.S. strategic triad and dual-capable aircraft, develop new small-yield warheads, create sealaunched cruise missiles, and reinforce the C3 systems to support them. These initiatives go along with the new expanded understanding of “extreme circumstances” which allow for a U.S. nuclear response to a non-nuclear attack, as well as with other new features of the U.S. nuclear doctrine: the creation of “more  usable”  types of nuclear weapons, the integration of nuclear and conventional elements of planning and  operations, the enhanced focus on cyber threats, and the prioritization of “flexibility,” “uncertainty,” and “hedging” – which all increase the danger of an actual use of nuclear weapons. The NPR presents Russia as a higher threat compared to China, while China – as a major challenge to the United States in the Asian region. Yet the NPR does not call these two states “adversaries”  and  stresses the need to avoid confrontation and an arms race. Besides Russia’s  “aggressive  policies,”  military programs and bellicose declarations, the NPR focuses on its alleged adherence to the concept of “escalation for de-escalation”  – early first use of nuclear weapons to end a conventional conflict on favorable terms – a notion that the NPR sets to counteract. The requirements  formulated by the NPR towards Iran and North Korea include ensuring their non-nuclear status, countering their growing influence in the respective Middle East and Asia-Pacific regions, preventing the transfer of nuclear and missile technologies and sensitive materials to third parties and states, and convincingly demonstrating that their aggression, including a conventional one, would be met with resolute action by the United States and its allies. Yet, in a shuffle of a kind, opposite to how the Obama Administration renounced military solution to the Iran problem and chose negotiations with this country with no preliminary condition, – and at the same time preferred the tactics of isolating North Korea and disregarding its claims, – now it is with Seoul that Washington  may engage with, while simultaneously demonstrating a tough line towards Teheran. Yet the shifts towards a settlement on the Korean Peninsula, along with certain signs of restraint in the NPR, offer some grounds to hope that  – given political will and active international  efforts – the worst-case scenarios and  further deterioration of international  situation may successfully be avoided.